(untitled) (Research, Society and Development, 2022)
The objective of this work was to analyze the urbanized environment, to recognize the importance of the area and its relationship with humans, identify the DAP and CAP of each tree, as well as lichen colonies and tiller number. Data collection was carried out in September 2017, in ​​1790m2 belonging to the Dom Constantino Luers Green Area Corridor located in the municipality of Arapiraca - AL. The study area presents distributed throughout the site, 22 trees to be registered were enumerated according to their location. CAP measurements - circumference at breast height and DBH - diameter at breast height were evaluated, counting the number of tillers per tree and identifying the lichen coloniesfound on the trunks of five trees, in which a square was constructed of dimensions 20x30cm using masking tape, being applied in a random region of the trunk of the trees in which the largest number of colonies was found. The 22 trees analyzed in the Green Area in the municipality of Arapiraca - AL showed variation in the CAP and DAP measures. Only two trees presented equal measures for the DAP value and four trees presented the same values ​​in the CAP. Regarding tillers, most trees have only two tillers per species. Of the five individuals chosen for the analysis of lichen coverage, only one presented a greater number of colonies, as even some of them presented a lower amount of lichens than the others.